A Novel Two-Velocity Method for Elaborate Isokinetic Testing of Knee Extensors - Grbic, Vladimir; Djuric, Sasa; Knezevic, Olivera M.; Mirkov, Dragan M.; Nedeljkovic, Aleksandar; Jaric, Slobodan (International Journal of Sports Medicine, 2017)
Single outcomes of standard isokinetic dynamometry tests do not discern between various muscle mechanical capacities. In this study, we aimed to (1) evaluate the shape and strength of the force-velocity relationship of knee extensors, as observed in isokinetic tests conducted at a wide range of angular velocities, and (2) explore the concurrent validity of a simple 2-velocity method. Thirteen physically active females were tested for both the peak and averaged knee extensor concentric force exerted at the angular velocities of 30°–240°/s recorded in the 90°–170° range of knee extension. The results revealed strong (0.960<R<0.998) linear force-velocity relationships that depict the maximum muscle force (i.e. the force-intercept), velocity (velocity-intercept), and power (their product). Moreover, the line drawn through only the 60° and 180°/s data (the ‘2-velocity method’) revealed a high level of agreement with the force-velocity relationship obtained (0.76<R<0.97; all power<0.001); while the force-intercept highly correlated (0.68<R<0.84; all power≤0.01) with the directly measured isometric force. The 2-velocity method could therefore be developed into a standard method for isokinetic testing of mechanical capacities of knee extensors and, if supported by further research, other muscles. This brief and fatigue-free testing procedure could discern between muscle force, velocity, and power-producing capacities.
Keywords: muscle; force; velocity; power; quadriceps; linear regression